The Relationship between Tourism and Economic Growth of Thailand: A Case Study of Economic Growth by Industrial Origin - Jatuporn, Chalermpon; Sinnarong, nirote; Nunthasen, Waraporn; Nunthasen, Ke (Business Administration and Management Journal Review, 2023)
The purpose of this study is to analyze the relationship between tourism and economic growth by industrial origin including agriculture, manufacturing, and service. The quarterly time series is employed over the period of 1993:Q1 to 2018Q4, a total of 92 observations as well as an analysis using time series techniques consist of (1) stationary test of data by the ADF unit root, (2) long-run equilibrium relationship analysis by the Cointegration, and (3) short-run adjustment by the Error Correction Model (ECM) respectively. The results show that economic growth as a whole and service sector have a long-run equilibrium relationship with tourism, while economic growth in agriculture and industry has a short-run relationship with tourism. The model can explain the overall economic growth including agricultural, manufacturing, and service sectors based on tourism variables as 92.564%, 82.231%, 86.844%, and 95.366% respectively.